The Association between Endotoxin and Lung Function among Children and Adolescents Living in a Rural Area - Joshua A Lawson; James A Dosman; Donna C Rennie; Jeremy Beach; Stephen C Newman; Ambikaipakan Senthilselvan (Canadian Respiratory Journal)
Increased levels of endotoxin found in rural and agricultural areas are an environmental exposure believed to cause a paradoxical proinflammatory effect on respiratory health that can exacerbate asthma. Previous studies involving adults have demonstrated an association between high endotoxin levels and lower lung function. Apart from occupational settings, however, few studies have investigated the relationship between lung function and endotoxin exposure, such as environmental tobacco smoke, especially in children. This study examined the modifying effects of sex, pre-existing asthma and other environmental exposures, including tobacco smoke, in children living in rural communities in Saskatchewan.